Effect of temperatures, overwrap materials, and chemical coatings on prepackaged Elberta peaches - Ornelas, Manuel R., author; Jorgensen, Carl L., advisor; Binkley, A. M. (Almond Madison), 1900-, committee member; Heilig, Herb, committee member; Burdick, R. T. (Raymond Terry), 1889-1982, committee member; Gardner, Robert, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Peach; Fruit -- Marketing